THE INTERACTION BETWEEN CRITICAL THINKING SKILLS AND MATHEMATICAL COMMUNICATION SKILLS OF PRE-SERVICE TEACHER IN SOLVING HOTS PROBLEMS FOR DISCRETE MATHEMATICS COURSES - Selvia Erita; Eline Yanty Putri Nasution; Rilla Gina Gunawan (UIN Imam Bonjol Padang, 2026)
This study aims to analyse the interaction between student critical thinking skills and mathematical communication skills in solving higher order thinking skills (HOTS) problem for discrete mathematic course. This research emphasizes the interaction effect between the two skills. This study employed a sequential explanatory mixed-method design involving 42 undergraduate students. Data were collected through HOTS based essay test, interviews and observations. Quantitative data were analysed using two ways ANOVA, followed by qualitative analysis to explore student thinking process. The results show that there is statically significant interaction effect between critical thinking skills and mathematics communication (p